2019
DOI: 10.1038/s41467-019-13315-x
|View full text |Cite
|
Sign up to set email alerts
|

The targetable kinase PIM1 drives ALK inhibitor resistance in high-risk neuroblastoma independent of MYCN status

Abstract: Resistance to anaplastic lymphoma kinase (ALK)-targeted therapy in ALK-positive non-small cell lung cancer has been reported, with the majority of acquired resistance mechanisms relying on bypass signaling. To proactively identify resistance mechanisms in ALK-positive neuroblastoma (NB), we herein employ genome-wide CRISPR activation screens of NB cell lines treated with brigatinib or ceritinib, identifying PIM1 as a putative resistance gene, whose high expression is associated with high-risk disease and poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…Other mutations included NRAS, BRCA1/2 , APC , MAP3K1 , BRAF , and CDKN2A/B copy-number variants ( Yoda et al 2018 ). Specific to neuroblastoma, bypass signaling pathways such as activation of AXL ( Debruyne et al 2016 ), PIM1 ( Trigg et al 2019 ), EGFR, and ERBB4 ( Redaelli et al 2018 ) have been reported in association with ALK TKI resistance. As the ALK F1174L mutation persisted in our patient after relapse on lorlatinib, ALK-independent mechanisms were the likely drivers of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Other mutations included NRAS, BRCA1/2 , APC , MAP3K1 , BRAF , and CDKN2A/B copy-number variants ( Yoda et al 2018 ). Specific to neuroblastoma, bypass signaling pathways such as activation of AXL ( Debruyne et al 2016 ), PIM1 ( Trigg et al 2019 ), EGFR, and ERBB4 ( Redaelli et al 2018 ) have been reported in association with ALK TKI resistance. As the ALK F1174L mutation persisted in our patient after relapse on lorlatinib, ALK-independent mechanisms were the likely drivers of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis again highlighted our finding of MEIS2 as a putative key early dependency during murine TH-MYCN-driven neuroblastoma. In addition, other putative interesting candidates include amongst others CBX2 (a core PRC1 subunit required for binding to H3K27me3 marked domains), CDCA8 (a subunit of the “Chromosomal Passenger complex” (CPC) and direct MYCN target gene contributing to the aggressive phenotype of MYCN-amplified neuroblastoma [ 77 ]), Claspin (a key mediator of the ATR-CHK1 pathway), and PIM1 (a key driver of ALK inhibitor resistance in neuroblastoma [ 78 ]). Last, our study defined for the first time through a cross-species integrative transcriptomics approach putative master regulators for MYCN-driven neuroblastoma tumor development and revealed FOXM1 and the DREAM complex members MYBL2 and E2F8 as top-scoring candidates.…”
Section: Discussionmentioning
confidence: 99%
“…PDX models of ALK mutant neuroblastoma have been pivotal in recommending particular ALK targeting small molecules for clinical studies. Of particular note, the Felix neuroblastoma PDX, which was established post-mortem from the blood of a patient who died of ALK F1245C MYCN -non-amplified high-risk neuroblastoma, has been part of several publications to highlight the potential of synergy between ALK inhibition and chemotherapy [ 76 ], the resistance to ALK inhibition mediated by Pim1 [ 77 ], and the study of novel ALK-antibody conjugates [ 78 ]. The Felix neuroblastoma PDX harbours the third most common ALK mutation found in neuroblastoma, and it exhibits de novo resistance to the first generation ALK inhibitor, crizotinib, which mirrors that seen clinically for this subgroup of patients.…”
Section: The Development and Refinement Of Patient-derived Models For Neuroblastomamentioning
confidence: 99%
“…Extensive model characterisation should be undertaken at each in vivo passage to characterise molecular concordance with the patient tumour and exclude the possibility of murine EBV-associated lymphoma [ 41 , 42 , 43 , 44 , 45 , 52 , 72 ]. At this point, the possibilities for utilisation of a successful neuroblastoma PDX model are far-reaching and include the study of clonal dynamics [ 47 , 48 , 49 , 50 ], preclinical drug testing [ 34 , 35 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], and immunological studies by using humanized mice or switching the mouse strain for further engraftment [ 80 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Figurementioning
confidence: 99%